Losses and gains to developing countries from the migration of educated workers: an overview of recent research, and new reflections - Oded Stark; C. Simon Fan (University of Bonn, Center for Development Research (ZEF), 2007)
This paper synthesizes and extends recent research on The New Economics of the Brain Drain. In a unified framework, the paper shows that while recently identified adverse repercussions of the brain drain exacerbate the long-recognized impacts of the brain drain, longer-term consequences turn the brain drain into the harbinger of powerful gains. These gains have been studied already in recent research, or merit attention in future research. – – Dieser Aufsatz bietet eine Darstellung und Erweiterung der jüngsten Forschungsarbeiten zum Thema ”The New Economics of the Brain Drain”. Die Autoren zeigen in einem vereinheitlichen Rahmen: während kürzlich erkannte ungünstige Auswirkungen des Brain Drain seine lang bekannten negativen Folgen verstärken, führt der Brain Drain längerfristig hingegen zu enormen Gewinnen. Diese Gewinne wurden bereits kürzlich wissenschaftlich untersucht bzw. sollten verstärkt auch in künftiger Forschung Beachtung finden.
Keywords: 330; Brain Drain; Hochqualifizierte Arbeitskräfte; Entwicklungsländer